2021
DOI: 10.1002/jimd.12429
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic confidence scheme for CLN3 disease

Abstract: Over the past 20 years, diagnostic testing for genetic diseases has evolved, leading to variable diagnostic certainty for individuals included in long‐term natural history studies. Using genotype and phenotype data from an ongoing natural history study of CLN3 disease, we developed a hierarchical diagnostic confidence scheme with three major classes: Definite, Probable, or Possible CLN3 disease. An additional level, CLN3 Disease PLUS, includes individuals with CLN3 disease plus an additional disorder with a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…It will fall to future work to determine what the perceptual and cognitive implications of this breakdown are [ 10 ] [ 11 ] [ 70 ]. However, prior work has shown that weakened ability to sustain information in sensory memory can reflect cognitive deterioration in various clinical conditions [ 42 ] [ 45 ] [ 46 ]. It will also be of significant interest to further investigate the duration-evoked MMN at even slower presentation rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will fall to future work to determine what the perceptual and cognitive implications of this breakdown are [ 10 ] [ 11 ] [ 70 ]. However, prior work has shown that weakened ability to sustain information in sensory memory can reflect cognitive deterioration in various clinical conditions [ 42 ] [ 45 ] [ 46 ]. It will also be of significant interest to further investigate the duration-evoked MMN at even slower presentation rates.…”
Section: Discussionmentioning
confidence: 99%
“…All participants with CLN3 disease underwent detailed phenotypic assessment, accompanied by detailed medical history questionnaires completed by their caregivers. All had clinically definite CLN3 disease [ 46 ] . Symptom severity was measured using a disease-specific instrument, the Unified Batten Disease Rating Scale (UBDRS) [ 8 ] [ 9 ] and severity stage was assigned using the CLN3 Staging System ( CLN3 SS) [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…NCLs are classified as congenital, infantile (INCL), late infantile (LINCL), juvenile (JNCL), and adult (ANCL) NCLs according to the clinical presentation age of the disorder [Masten et al, 2021].…”
Section: Discussionmentioning
confidence: 99%